Métaperception en milieu scolaire : quand les élèves anticipent la catégorisation de l’enseignant - Stephen Gagnepain (Recherches en Éducation)
Métaperception research’s (i.e., beliefs that an individual develops about the perception of others about him) in school context are uncommon. Research about student’s metaperceptions could be used to characterize the influence of variables (amount of informations, etc.) involved in teacher’s expectations and judgements. The proposed research examines students’ metaperceptions when relying on a teacher’s beliefs. The research compares teacher’s categorization of students and the students’ métaperceptions. Three measures related with progressive presentation of information on teacher’s categorization show convergence between student metaperception and teacher categorization: these measures highlight the variation in the meta-accuracy and group membership metaperception of students (i.e. the categories selected by the student as representative of the teacher’s perception of each measure). The results highlight that the majority of students do not accurately identify the teacher’s categorization. This inaccuracy is not dependent on the information they have on the categorization of the teacher. The analysis of the convergence of student’s metaperceptions with the teacher’s categorization shows that the progressive provision of information on teacher’s categorization does not significantly influence meta-accuracy of students. Despite this, the analysis of how students change or stabilize their métaperspectives positions during experimental modalities shows that the proportion of students who modulate their group membership metaperception varies significantly between experimental modalities. The information available on teacher’s categorization influences group membership metaperception of students. Nevertheless, this influence is moderate.